Presence of aggregates of smooth endoplasmic reticulum in MII oocytes affects oocyte competence: molecular-based evidence. (9th April 2018) - Stigliani, Sara; Moretti, Stefano; Casciano, Ida; Canepa, Pierandrea; Remorgida, Valentino; Anserini, Paola; Scaruffi, Paola
Abstract: STUDY QUESTION: Does the presence of aggregates of smooth endoplasmic reticulum (SERa) impact the transcriptome of human metaphase II (MII) oocytes?. SUMMARY ANSWER: The presence of SERa alters the molecular status of human metaphase II oocytes. WHAT IS KNOWN ALREADY: Oocytes presenting SERa are considered dysmorphic. Oocytes with SERa (SERa+) have been associated with reduced embryological outcome and increased risk of congenital anomalies, although some authors have reported that SERa+ oocytes can lead to healthy newborns. The question of whether or not SERa+ oocytes should be discarded is still open for debate, and no experimental information about the effect of the presence of SERa on the oocyte molecular status is available. STUDY DESIGN, SIZE, DURATION: This study included 28 women, aged <38 years, without any ovarian pathology, and undergoing IVF treatment. Supernumerary MII oocytes with no sign of morphological alterations as well as SERa+ oocytes were donated after written informed consent. A total of 31 oocytes without SERa (SERa−) and 24 SERa+ oocytes were analyzed. PARTICIPANTS/MATERIALS, SETTING, METHODS: Pools of 8–10 oocytes for both group were prepared. Total RNA was extracted from each pool, amplified, labeled and hybridized on oligonucleotide microarrays. Analyses were performed by R software using the limma package. MAIN RESULTS AND THE ROLE OF CHANCE: The expression profiles of SERa+ oocytes significantly differed from those of SERa− oocytes in 488 probe sets corresponding to 102 down-regulated and 283 up-regulated unique transcripts. Gene Ontology analysis by DAVID bioinformatics disclosed that genes involved in three main biological processes were significantly down-regulated in SERa+ oocytes respective to SERa− oocytes: (i) cell and mitotic/meiotic nuclear division, spindle assembly, chromosome partition and G2/M transition of mitotic cell cycle; (ii) organization of cytoskeleton and microtubules; and (iii) mitochondrial structure and activity. Among the transcripts up-regulated in SERa+ oocytes, the most significantly ( P = 0.002) enriched GO term was 'GoLoco motif', including the RAP1GAP, GPSM3 and GPSM1 genes. LARGE SCALE DATA: Raw microarray data are accessible through GEO Series accession number GSE106222 (https://www.ncbi.nlm.nih.gov/geo/query/acc.cgi?acc=GSE106222 ). LIMITATIONS, REASONS FOR CAUTION: Data validation in a larger cohort of samples would be beneficial, although we applied stringent criteria for gene selection (fold-change >3 or <1/3 and FDR < 0.1). Surveys on clinical outcomes, malformation rates and follow-up of babies born after transfer of embryos from SERa+ oocytes are necessary. WIDER IMPLICATIONS OF THE FINDINGS: We provide information on the molecular status of SERa+ oocytes, highlighting possible associations between presence of SERa, altered oocyte physiology and reduced developmental competence. Our study may offer further information that can assist embryologists to make decisions on whether, and with what possible implications, SERa+ oocytes should be used. We believe that the presence of SERa should be still a 'red flag' in IVF practices and that the decision to inseminate SERa+ oocytes should be discussed on a case-by-case basis. STUDY FUNDING/COMPETING INTEREST(s): This study was partially supported by Ferring Pharmaceuticals. The authors have no conflicts of interest to declare.